Fluoroiodomethane: A CH2F‐Moiety‐Delivering Agent Suitable for Nucleophilic‐, Electrophilic‐, and Radical‐Harnessed Operations. Issue 17 (5th August 2022) - Senatore, Raffaele; Malik, Monika; Pace, Vittorio
Abstract: The recent renewed interest in mono‐fluoromethylation chemistry – somehow less developed than the analogous well‐established trifluoro‐ and difluoro‐methylation tactics – identified the simple C1 building block fluoroiodomethane as an effective and versatile CH2 F‐delivering agent. The convenient physical state – liquid with a boiling point of 53 °C – and the nowadays commercial availability, boosted in the last years the flourishing of protocols where it is used for generating the fluoromethyl group under conceptually distinct logics: electrophilic, nucleophilic, and radical. Depending on the reaction conditions adopted, the reagent serves as a pluripotent precursor of variously functionalized CHF fragments, thus considerably simplifying the installation of the motif into organic skeletons. A critical analysis of the applications found by the reagent in the literature (mainly) published in the last 5 years is provided with vistas to its employment in the preparation of drug molecules (and precursors thereof). Abstract :